Prevalence of Cardiovascular Risk Factors among Taxi Drivers in Yazd, Iran, 2016 - Vida Rezaei Hachesu; Shadi Naderyan Feli; Mohammad Javad Zare Sakhvidi (Shahid Sadoughi University of Medical Sciences, 2017)
Abstract Introduction: Cardiovascular diseases are the first cause of death in the worldwide. Taxi drivers are a high risk group for developing cardiovascular disease, due to exposure to unhealthy working conditions. The aim of this study was to assess the prevalence of cardiovascular risk factors among taxi drivers. Methods: This cross-sectional study in 2016, was conducted on 110 taxi drivers that selected by simple random sampling method. Prevalence of dyslipidemia, obesity, smoking, hypertension and diabetes were estimated. Descriptive statistics and the extended Fisher exact test were used for data analysis. Results: In this study, all participants were male, with mean age and experience 46.4±11.6 and 11.3±8.8 years, respectively. Among all subjects, 89.1% of people had at least one risk factor, 30% two risk factors, 22.7% three risk factors, 14.5% four risk factors and 4.5% five risk factors. This study showed that prevalence of hypertension, diabetes, dyslipidemia and smoking among subjects were 35.5, 10, 66.4 and 12.7, respectively. Also 45.45% and 25.45 % of individuals were overweight and obese, respectively. Conclusion: The results of this study showed a high prevalence of cardiovascular risk factors (especially low HDL-C) among taxi drivers. Training courses in order to lifestyle modification can be effective for preventing the occurrence of cardiovascular diseases in these people.   Keywords: Taxi drivers, Risk factors, Cardiovascular disease